Penggunaan Media Gambar Seri (Flow Chart) Untuk Peningkatan Kemampuan Membaca Pemahaman Pada Murid Tunarungu Kelas Dasar III SLB Negeri I Barru - Nurul Rahma; Usman Usman; Mustafa Mustafa (-, 2023)
This study examines the ability on reading comprehension of deaf students in the Indonesian subject at SLB Negeri 1 Barru. The formulation of the problem in this study is there an increase in the reading comprehension ability of deaf students in Elementary Class III SLB Negeri I Barru after using the flow chart media? The purpose of this study is to determine learning outcomes. reading comprehension of deaf elementary class III students at SLB Negeri 1 Barru before using the serial picture media (flow chart). 2) The results of learning to read the understanding of deaf elementary class III students at SLB Negeri 1 Barru when using serial picture media (Flow chart). 3) The results of learning to read comprehension of elementary class III deaf students at SLB Negeri 1 Barru after using the media picture series (Flow chart). 4) Comparison of the results of learning to read comprehension of deaf elementary class III students at SLB Negeri 1 Barru in the phase before using the media picture series (Flow chart), when applying the media picture series (Flow chart) and after using the media picture series. This study used the Single Subject Research (SSR) experimental method with an A-B-A research design. The data collection technique used is the action test. The subject in this study was a class III deaf student at SLB Negeri 1 Barru with the initials AKQ. The conclusions from this study are as follows: to find out: 1) The ability to read the subject's understanding before giving interventions in the form of using picture series media (flow charts) is in the underprivileged category. 2) The ability to read the subject's understanding in the intervention phase in the form of using picture series media (flow chart) is in the very capable category. 3) The ability to read the subject's understanding after giving the intervention in the form of using Picture Series media (Flow chart) is in the very capable category. 4) Improving the ability to read comprehension in Class III Deaf Children at SLB Negeri 1 Barru Based on the results between conditions, namely in the conditions before being given treatment (baseline 1) the ability to read comprehension of being unable to increase to the high category is very capable in conditions while being given treatment (intervention). and in the conditions during which the treatment was given (intervention (B) ) the ability to read comprehension after being given treatment (baseline 2) the child remained in the very capable category, but the score obtained by the AKQ subject was higher than before being given treatment (baseline).